DEVELOPMENT STRATEGY IN CIREBON USING TAWHIDI METHODOLOGY STRING RELATION - Siti Komara (Green Publisher, 2022)
Development about amount traveler Muslims who continue increase be one _ potency big for could interesting interest they visit to a particular region or country . Policies that govern about Halal tourism is also made by the Government , one of which is is indicator halal tourism that requires existence religious symbols in travel . Study this aim for see halal travel with perspective different , no only use indicator halal tourism that has been formulated by the government but also with use methodology Tawhidi String Relations, a method view that uses aspect interaction , integration and evolution for realize sustainability and well- being for the actors involved in halal tourism . So that